The protective function of galectin‐9 in liver ischemia and reperfusion injury in mice. Issue 7 (July 2015) - Hirao, Hirofumi; Uchida, Yoichiro; Kadono, Kentaro; Tanaka, Hirokazu; Niki, Toshiro; Yamauchi, Akira; Hata, Koichiro; Watanabe, Takeshi; Terajima, Hiroaki; Uemoto, Shinji
<x xml:space="preserve">Abstract</x> Galectin‐9 (Gal‐9) has gained attention as a multifaceted player in adaptive and innate immunity. To elucidate the role of Gal‐9, we used a mouse model of partial liver ischemia/reperfusion injury (IRI) with wild type (WT) and Gal‐9 knockout (KO) mice as well as a recombinant galectin‐9 (reGal‐9) protein. We found that the expression of Gal‐9 was enhanced endogenously in the liver especially by hepatocytes and Kupffer cells during warm IRI for a mouse liver, which causes massive destruction of liver tissue. Gal‐9 was released into the extracellular space in the liver and the highest levels in the plasma at 1 hour after reperfusion. The present study elucidates a novel role of Gal‐9 signaling in mouse liver IRI, by using Gal‐9–deficient mice and a stable form of reGal‐9 protein. In the circumstance of Gal‐9 absence, liver damage due to ischemia/reperfusion (IR) exacerbated the severity as compared with WT. On the other hand, exogenously administered reGal‐9 significantly ameliorated hepatocellular damage. It decreased the local infiltration of the inflammatory cells such as T cells, neutrophils, and macrophages, and it reduced the expression of proinflammatory cytokines/chemokines; then, it strongly suppressed the apoptosis of the liver cells. Interestingly, severe liver damage due to IR in Gal‐9 KO mice was improved by the administration of reGal‐9. In conclusion, Gal‐9 engagement ameliorated local inflammation and liver damage induced by IR, and the present study suggests a significant role of Gal‐9 in the maintenance of hepatic homeostasis. In conclusion, targeting Gal‐9 represents a novel approach to protect from inflammation such as liver IRI. Exogenous Gal‐9 treatment will be a new therapeutic strategy against innate immunity‐dominated liver tissue damage. Liver Transpl 21:969‐981, 2015. © 2015 AASLD.